ANALYZING THE GAP BETWEEN PRE-PURCHASE AND POST-PURCHASE CONSUMER PERCEPTIONS OF BRAND POSITIONING IN THE MOBILE TELECOM SECTOR - Dange, Kalyani; Chib, Shiney (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the intriguing gap between pre-purchase and post-purchase consumer perceptions, specifically within the context of brand positioning in the mobile telecommunications industry. In today’s highly competitive market, where consumer choices are abundant, understanding how consumers perceive a brand before and after purchase is crucial for brand managers to position their offerings effectively. Through a mixed-methods approach that combines qualitative interviews and quantitative surveys, this study examines the factors contributing to variance in consumer perception and their implications for brand positioning strategies. Findings reveal significant disparities between pre-purchase expectations and post-purchase experiences, shedding light on the challenges and opportunities for mobile telecom network providers in managing consumer perceptions throughout the customer journey.